Pengaruh Pertumbuhan Perusahaan, Kebijakan Dividen dan Struktur Modal terhadap Profitabilitas pada Perusahaan Perbankan yang Terdaftar di BEI (Periode 2021-2023) - Purba, Christyne Lourenza; Maithy, Sifera Patricia (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study was conducted to determine the extent to which company growth, dividend policy, and capital structure influence profitability in the banking sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The independent variables in this study include Company Growth (Company Growth), Dividend Policy (Dividend Payout Ratio), and Capital Structure (Debt to Equity Ratio). Meanwhile, profitability as the dependent variable is measured using Return on Assets (ROA). This research uses a quantitative approach with multiple linear regression analysis. A total of 39 observations were collected from 13 banks selected as the research sample. To ensure the accuracy of the model used, classical assumption tests such as normality, heteroscedasticity, and multicollinearity tests were conducted. The analysis results indicate that capital structure has a negative and significant effect on profitability, while company growth has a positive and significant effect. On the other hand, dividend policy does not have a significant impact on profitability. Overall, these three independent variables simultaneously influence the profitability of the companies.